Effect of Bio-Controlling Methods (Proplis and Bacteria) on the 3rd_larval Instar of Galleria mellonella (Lepidoptera: Pyralidae) - Wegdan Abass Hussien; Abubaker Haroun Mohamed Adam; Siefaldinn Mahammed Khaeir; Abd Elbagi Elsayed Ali (Journal of Agronomy Research, 2023)
The greater wax moth (Galleria mellonella L.) is one of the most destructive insect pests that threaten apiculture. Laboratory experiments were conducted in the Research Laboratory, College of Agricultural Studies, Sudan University of Science and Technology during the period from the 2nd_ of April to 29th_ of October 2021 to evaluate the lethal effect of Bee glue (proplis) and Bacillus thuringiensis var. Kurstaki (Btk) on the G.mellonella. Five concentrations (5%, 7.5%, 10%, 12.5% and 15%) of proplis extract and (0.62,1.25,2.5,5 and 10 mg/ml) of Bt were used for each proplis extract and Bt in a Completely Randomized Design. Powder ethanol extract of proplis at 15% concentration caused 83.3% mortality after 96 hrs of application, where as 10mg//ml concentration of Bt gave 93.3% mortality after 72 hrs of exposure. The statistical analysis revealed significant differences between all treatments and control. Additionally, all treatments (proplis/ /Bt) increased the mortality %.
Keywords: Bacillus thuringiensis